Corn, sorghum grain, wheat, rye, and barley as concentrates in complete pelleted rations compared with a standard nonpelleted sorghum grain and alfalfa hay ration for self-feeding fattening lambs - Menzies, C.S.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Previous experiments at this station have shown that lambs fed complete pelleted rations make faster, more efficient gains than lambs fed similar nonpelleted rations, and that optimum results are obtained when pelleted rations contain around 30 to 40 percent concentrates. This test was designed to study various grain sin complete pelleted rations compared with a standard nonpelleted ration.
Keywords: Sheep; Gain; Pelleted vs. nonpelleted rations